Spectrum of obstetric referral and their outcome at a Tertiary Care Center of Eastern Uttar Pradesh: An insight - Ankita Kumari; Mitra, Shaila; Vani Aditya (Asian Journal of Medical Sciences, 2022)
Background: Pregnancy and childbirth, especially in high-risk women, necessitate proper antenatal, intranatal, and immediate postpartum care. Early detection of complications and prompt referral to the higher level of care can reduce the associated adverse maternal outcomes. Aims and Objectives: The aim of the study was to evaluate the spectrum of pregnancy-related referrals to our hospitals and their outcomes. Materials and Methods: A prospective observational study was conducted in the Department of Obstetrics and Gynecology, B.R.D Medical College, Gorakhpur, U.P, India, over a period of 1 year (October 2020–September 2021). All the referred cases of obstetric indications ≥28 weeks of gestation were analyzed for reasons of referral and their outcomes. Results: Obstetrics referral accounted for 31.15% of the total obstetrics admissions (1416/4545). The average age of study participants was 26.92 years and majority being primigravida. The major reasons for referring patient were hypertensive disorders of pregnancy (16.74%), previous cesarean section (12.78%), and severe anemia (7.70%). There were 70 maternal deaths leading to case fatality rate of 4.94% while 94.2% of patient were discharged healthy. Conclusion: Lack of knowledge, ignorance, and poor transport facilities are major contributors of poor pregnancy outcome. Timely and appropriate referral is crucial in improving maternal outcome. Improvement in the quality of Maternal Child Health care at Primary Health Centre, Community Health Centre level; regular training of health-care providers in emergency obstetrics care is required to curb unnecessary referrals and consequently in reducing fetomaternal morbidity and mortality.